Occupational therapy in overweight and obesity care: Australian perspectives from a mixed methods study - Kieva Richards; Olivia Beattie; Danielle Hitch; Genevieve Pepin (Taylor & Francis Group, 2024)
Background Obesity and being overweight can hinder participation in daily activities and impact engagement. Occupational therapists offer a unique perspective on this issue, yet their practice is seldom described in the literature.Aim To explore how Australian occupational therapists use their occupational perspective when working with people who are obese or overweight.Methods A qualitative dominant crossover mixed methods approach was adopted. Eleven semi-structured interviews with occupational therapists were conducted and analysed. Questions explored clinical decision-making, barriers, facilitators, and therapist knowledge and confidence about working with these clients. Three Likert scale questions on client contact frequency, perceived intervention effectiveness and knowledge of weight-related occupational therapy provided contextualisation.Results Occupational therapists reported average confidence and variability in the effectiveness of weight-related interventions. Three key themes were identified: 1) Exploring clients' needs for weight management; 2) Incorporating weight management strategies in occupational therapy intervention; and 3) Organisation of current occupational therapy practice for people with obesity.Conclusion Occupational therapists should leverage an occupational perspective to enhance participation and engagement for people with obesity, thereby ensuring the client's best interests are met.Significance As change agents, occupational therapists can advocate for shifts in care culture, influence leadership and challenge systemic issues that limit occupational performance and participation for people with obesity.